Variation in Dorsal Fin Morphology in Common Bottlenose Dolphin Tursiops truncatus (Cetacea: Delphinidae) Populations from the Southeast Pacific Ocean - Van Waerebeek, Koen (2017)
We succinctly summarize population ID information for common bottlenose dolphins Tursiops truncatus of the Pacific coast of South America, covering four coastal range states. Phylogenetic uncertainties relate primarily to offshore vs. coastal (inshore) ecotypes and biogeographic borders between the five proposed populations (2 offshore, 3 coastal): Colombia-Ecuador Offshore stock (probably = ETP Offshore), Peru-Chile Offshore, Ecuador Coastal, Peru Coastal and an unique community (Pod-R) on the north-central coast of Chile. Main questions concern the extent of gene flow between the offshore stocks at one hand, and with -and between- the three coastal populations at the other hand. Seven cranial characters, four non-metric (separation of occipital condyles, pterygoid bone development, exostosis of periotic) and three metric (tooth width, antorbital process length, maximum width palatines), dorsal fin shape, body stockiness, mt-DNA (control region), habitat, prey composition, parasite load, behaviour and prevalence of some infectious diseases differentiate coastal from offshore forms. 'Pod-R' is the southernmost (29°15'S) and only confirmed coastal form community in Chilean waters, albeit with an offshore (falcate) dorsal fin. Bottlenose dolphins which regularly transit nearshore in the Lagos and Aysén regions (Chilean Patagonia) and occasionally enter deep fjords, present an offshore morphotype. We suggest that two other coastal areas in Chile where bottlenose dolphins have been documented over decades, one a ca. 60 km stretch of coastline centered at Valparaiso/Laguna Verde (33°10'S) in central Chile, and a 190 km coastline around the Mejillones Peninsula (23°10'S) in northern Chile, may not host coastal but offshore form animals. The continental border of the Atacama Trench off northern and northcentral Chile leaves an extremely narrow, steep shelf with nearshore deep water, locally with strong coastal upwelling and increased productivity. This habitat seems to attract oceanic cetaceans, including offshore T. truncatus, sperm whales, large balaenopterids, and other species. The southern distribution range of true coastal morphotype bottlenose dolphins in Pacific South America remains unknown but off Chile distance-to-shore may not be the reliable indicator of ecotype as it is further north in the study region.